The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fnsyn.2019.00024
|View full text |Cite
|
Sign up to set email alerts
|

LSO:Ce Inorganic Scintillators Are Biocompatible With Neuronal and Circuit Function

Abstract: Optogenetics is widely used in neuroscience to control neural circuits. However, non-invasive methods for light delivery in brain are needed to avoid physical damage caused by current methods. One potential strategy could employ x-ray activation of radioluminescent particles (RPLs), enabling localized light generation within the brain. RPLs composed of inorganic scintillators can emit light at various wavelengths depending upon composition. Cerium doped lutetium oxyorthosilicate (LSO:Ce), an inorganic scintill… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…ChR2 has been shown to be activated by wavelengths between 350 to 525 nm, with a peak at 470 nm (Lin et al, 2009;Bartley et al, 2019). Previously, we demonstrated that radioluminescent LSO:Ce microparticles are biocompatible with neuronal health and function (Bartley et al, 2019), and thus potentially useful for X-ray optogenetics.…”
Section: Lso:ce Radioluminescence Is Appropriate For Chr2mentioning
confidence: 97%
See 4 more Smart Citations
“…ChR2 has been shown to be activated by wavelengths between 350 to 525 nm, with a peak at 470 nm (Lin et al, 2009;Bartley et al, 2019). Previously, we demonstrated that radioluminescent LSO:Ce microparticles are biocompatible with neuronal health and function (Bartley et al, 2019), and thus potentially useful for X-ray optogenetics.…”
Section: Lso:ce Radioluminescence Is Appropriate For Chr2mentioning
confidence: 97%
“…ChR2 has been shown to be activated by wavelengths between 350 to 525 nm, with a peak at 470 nm (Lin et al, 2009;Bartley et al, 2019). Previously, we demonstrated that radioluminescent LSO:Ce microparticles are biocompatible with neuronal health and function (Bartley et al, 2019), and thus potentially useful for X-ray optogenetics. LSO:Ce has been widely studied as a scintillator, and has been shown to emit visible light in response to X-ray (Spurrier et al, 2007;Valais et al, 2008;Burdette et al, 2019).…”
Section: Lso:ce Radioluminescence Is Appropriate For Chr2mentioning
confidence: 97%
See 3 more Smart Citations